UNCERTAINTY REDUCTION STRATEGIES FOR PARENTS OF DAY CARE SERVICE USERS - Rahmadiana Rahmadiana; Salim Salim (Universitas Gunadarma, 2023)
Interpersonal communication typically involves two individuals engaging in dialogue, whether acquainted or unfamiliar. However, when individuals engage in conversation after a recent encounter, there is a tendency for uncertainty to arise. Uncertainty and anxiety surface when one lacks information about their conversational partner, compelling them to employ strategies to reduce this uncertainty. This study aims to elucidate the types of uncertainty experienced by parents utilizing the services of